Analysis of the Financial Thinking of the Population (On the Example of the Republic of Uzbekistan) - Nodira Isametdinovna, Khasankhonova (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the theory and practice of financial behavior using the example of the population of Uzbekistan. Financial thinking is the behavior, action, evaluation and ability to make decisions on investing funds. Therefore, a thorough study of financial thinking provides an answer to a number of questions, such as raising credit, investing cash in the population. When considering financial thinking, objective and subjective factors are described, such as confidence in the banking system, inflationary expectations affecting financial thinking and population behavior. The article also analyzes inflation expectations, population sentiment and liquidity in the banking system in the Republic of Uzbekistan. Of particular importance were such questions as in what form it is better to keep savings, intentions to take a loan, which show variability, analysis of the financial thinking of the population.